Die dorne Croene ons Heeren revisited: Een laatmiddeleeuws passiegebed uit de Nederlanden - Rossano, Bram (2023)
Die dorne Croene ons Heeren (‘The Crown of Thorns of our Lord’) is a fifteenth-century meditative prayer on the Passion, that was brought to light by D.A. Stracke in 1929. This article offers an update of its transmission, which enables a revision of the former classification and a better insight into the text. Furthermore, by textual analysis this prayer is placed in the context of the tradition and innovations of contemporary Passion literature.